2011
DOI: 10.1523/jneurosci.2740-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of Twenty/20 Vision in Reading

Abstract: One functional anatomical model of reading, drawing on human neuropsychological and neuroimaging data, proposes that a region in left ventral occipitotemporal cortex (vOT) becomes, through experience, specialized for written word perception. We tested this hypothesis by presenting numbers in orthographical and digital form with two task demands, phonological and numerical. We observed a main effect of task on left vOT activity but not stimulus type, with increased activity during the phonological task that was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Such top-down task-related effects have been reported in VWFA (Hellyer et al, 2011; Mano et al, 2013; Wang et al, 2011). However, even if it would turn out that the representation of lexical status in VWFA is task dependent, its observation under the current active task conditions still shows that lexicality is relevant to the internal organization of VWFA.…”
Section: Discussionsupporting
confidence: 55%
“…Such top-down task-related effects have been reported in VWFA (Hellyer et al, 2011; Mano et al, 2013; Wang et al, 2011). However, even if it would turn out that the representation of lexical status in VWFA is task dependent, its observation under the current active task conditions still shows that lexicality is relevant to the internal organization of VWFA.…”
Section: Discussionsupporting
confidence: 55%
“…We want to emphasize that the present DCM findings therefore do not imply irrelevance of top-down signals for the functioning of the left vOT in general. There is overwhelming evidence that in many cases of letter-string and visual object processing, top-down signaling is crucial for the left vOTs functional response [e.g., Devlin et al, 2006;Hellyer et al, 2011;Kherif et al, 2011;Mano et al, 2012;Reich et al, 2011;Twomey et al, 2011]. Still, the present study shows that bottom-up signaling is of theoretical importance for understanding the function of this area.…”
Section: Discussionmentioning
confidence: 44%
“…There is overwhelming evidence that in many cases of letter-string and visual object processing, top-down signaling is crucial for the left vOTs functional response [e.g., Devlin et al, 2006;Hellyer et al, 2011;Kherif et al, 2011;Mano et al, 2012;Reich et al, 2011;Twomey et al, 2011]. We observed that bottom-up signaling from the occipital cortex to the left vOT strongly increases for pseudohomophones.…”
Section: Discussionmentioning
confidence: 56%
“…Interestingly, McCrory et al (2005) found that dyslexic readers exhibited reduced local brain activation in the occipito-temporal cortex not only for word reading but also for picture naming. This indicates an impairment of a more general function which implies the left occipito-temporal cortex, namely the integration between visual and verbal information (see also Price and Devlin 2003 , 2011 ; Devlin et al 2006 ; Hellyer et al 2011 ; Kherif et al 2011 ). We found support for this hypothesis by showing permanently reduced connectivity between left occipito-temporal areas and the left IFG.…”
Section: Discussionmentioning
confidence: 99%